1980
DOI: 10.3382/ps.0590782
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Vitamin Requirements of the Domestic Fowl ,

Abstract: The basic vitamin requirements of the bird must be more clearly established before the true effects of temperature can accurately be measured. Although the literature reveals progress, the knowledge gained (as in many other fields of scientific investigation) is spotty, contradictory, vague, and intriguing, providing a basis for further planned comprehensive investigation. A review of literature leads to some general conclusions on the effects of temperature on vitamin requirements. 1) Feed consumption regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Supplementation of birds with vitamin A (Moreng, 1980), ascorbic acid (Kafri and Cherry, 1984;Pardue et al, 1985), and ammonium chloride (Balnave and Oliva, 1991) have all been shown to demonstrate a variable performance benefit under HT conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of birds with vitamin A (Moreng, 1980), ascorbic acid (Kafri and Cherry, 1984;Pardue et al, 1985), and ammonium chloride (Balnave and Oliva, 1991) have all been shown to demonstrate a variable performance benefit under HT conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports in the literature deal with ambient temperature effects in relation to dietary regimens (Cowan and Michie, 1977;Hurwitz et al, 1980;Moreng, 1980;Bacon et al, 1981;Charles et al, 1981;McNaughton and Reece, 1984). Most of these reports refer to the stress of elevated temperatures, which tends to reduce feed intake and in turn creates deficiencies of those nutrients essential for optimal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition manipulation of heat stress includes feeding timing (Teeter et al, 1987) quantity and quality of food, and fat supplementation (Hussein, 1996;Soliman et al, 1999;. Critical essential amino acids (Yanming and Baker, 1993), minerals and vitamins (Moreng, 1980), and feed additives and growth promoters (Teeter, 1995) play an important role in this respect.…”
Section: Introductionmentioning
confidence: 99%